POVERTY REDUCTION AND LIVELIHOOD IMPROVEMENT OF WOMEN THROUGH GOAT REARING - Rahman, Md. Matiur; Hossain, M. Mujaffar; Miah, M.A. Momen (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2017)
This study aimed to examine household in goat keeping farms having more than two goats with respect to its viability, socioeconomic characteristics of the women goat keepers, contribution of small scale goat farming to food security and livelihood, identify major problems associated with small scale goat famers. The study had been conducted in 6 villages namely Kandhapara, Hossainpur, Merigai, Horinadi Shimulia and Nagua of Phulpur upazila in Mymensingh district. In total 60 farmers comprising 07 medium, 43 poor and 10 most vulnerable or extreme poor farmers were randomly for the study. Primary data were collected from the selected farmers by interview method. Both tabular and financial analyses were done to achieve the objectives. The study revealed that most of the women were poor with small family size. However they were young and literate. The study clearly indicated that investment in goat farming were viable. The annual total cost of production per Black Bengal goat was BDT. 3,374, while gross return and net return per household were BDT.21,276 and BDT.17,902 respectively. It was observed that livelihood increased dramatically through goat rearing in the study area. Annual food purchasing capacity increased from 20 to 28 percent. The social status of the farmer?s family increases. Educational status, festival, health facilities acceptance were increased at 19%, 26% and 28% through goat. The position in the family, participation in social activities, water facilities and sanitation also increased remarkably. The study also identified that the goat farmers had been facing some crucial problems with goat keeping. If these problems could be overcome, all the goat farms would be able to earn a higher level of that of the existing level. It was clearly found that the women who reared goat had the most rapid improvement in livelihood.